The Effect of the Relating, Experiencing, Applying, Cooperating, and Transferring Learning Model on Students' Scientific Argumentation Skills - Wiwik Kartika Sari; Fadilah; R. Arizal Firmansyah; Kustomo (Jurnal Pendidikan Sains Indonesia, 2026)
Students’ scientific argumentation skills in learning reaction rate are still relatively low, indicating the need for an instructional model that actively engages students in constructing and justifying scientific claims. This study aims to analyze the effect of the relating, experiencing, applying, cooperating and transferring (REACT) learning model on students' scientific argumentation skills in reaction rate material and the effectiveness of the REACT learning model. The research method used was a quasi-experiment with a nonequivalent control group design. The samples in this study were students in classes XI, which were determined using cluster random sampling. Data collection techniques included tests, interviews, observations, and documentation. Data analysis used t-tests, N-Gain tests, and effect size tests. Based on the results of the hypothesis test using an independent t-test, a significance value (2-tailed) of 0.000 <0.05 was obtained. The results of this study indicate that the REACT learning model has an effect on students' scientific argumentation skills in reaction rate material of 59.7% with an effect size value of 1.41. Thus, the REACT learning model has a significant effect on students' scientific argumentation skills in reaction rate material